KAJIAN SIFAT FISIKO-KIMIA KARAGINAN DARI RUMPUT LAUT JENIS Eucheuma sp. DI PERAIRAN SULAWESI SELATAN - Fitri, Muhammad (Journal Galung Tropika, 2012)
The aim of this research is for determine the carrageenan physics-chemistry characteristic which resulted from seaweed Eucheuma sp. The based on region and season and identification carrageenan quality who resulted based on region and season. This research stage who applied is survey stage the cultivation locate seaweed Eucheuma sp. The observation stage and datum withdrawal appropriate with parameter who decided. Variable of factor A = The sampling withdrawal treatment with season difference is A1= The dry season (withdrawal sampling’s of Eucheuma cottoniiin June) and A 2 = The rain season (withdrawal sampling’s ofEucheuma cottoniiin November) ; Variable of factor B = the sampling withdrawal treatment with location difference, which B1 = The Bone waters, B2 = The Luwu waters, and B 3 = The Takalar waters. The concludearewithdrawalEucheuma cottonii seaweed based on dry season time the best carrageenan quality. The Bone waters where ash contents, sulfate ion contents, viscosity, sulfate contents, melting points (oC) and Pb , Cu, and Zn heavy metal the lowest while gel strength carrageenan the highest. In the rain season where ash contents, viscosity, sulfate contents, melting points (oC) and Zn heavy metal the lowest in Bone lowest, while gel strength carrageenan the highest.